HAK ATAS KESEHATAN BAGI WARGA NEGARA MISKIN DI SINGAPURA DALAM PERSPEKTIF HUKUM HAK ASASI MANUSIA INTERNASIONAL - Cahya Kartika Nugraha, I Gusti Agung Bagus; Laksmi Danyathi, Ayu Putu (Kertha Negara : Journal Ilmu Hukum, 2015)
Poor citizens in Singapore are increasingly squeezed by the high cost of healthcare.Ironically, Singapore is a developed country that is very popular with its medicaltourism. On one hand many foreigners come to Singapore for the purpose of healthcare(medical assistance), but in other hand its poor citizens are facing the unreachablemedical cost. This obviously a case of discrimination performed by the SingaporeGovernment to its citizens, particularly related to the right to health that has beenuniversally recognized under international law. This paper aims to analyze theexistence of the right to health from the perspective of international human rights law.In addition, this writing is also intended to analyze the legal obligations and moralresponsibilities of the Government of Singapore with regard to this issue.
Keywords: right to health, Singapore, international human rights law